In-situ fabrication of well-distributed gold nanocubes on thiol graphene as a third-generation biosensor for ultrasensitive glucose detection - Chu, Z.; Liu, Yu; Xu, Y.; Shi, L.; Peng, J.; Jin, W. (Pergamon, 2015)
Because of the advanced work mechanism on enzyme direct electron transfer, third-generation biosensor has aroused the growing attentions in recent decade. Herein, a novel structured 3rd generation glucose biosensor was constructed by the in-situ limited electrodeposition of gold nanocubes on a thiol graphene film. On account of the restriction from –SH group, initially, a tightly distributed Au seed layer was homogeneously formed to cover the graphene surface. Then 100 nm well-defined Au cubes were grown above with a uniform distribution, resulting in the low electrochemical resistance. Due to the synergistic effects of uniform distribution and regular nanostructure, the as-prepared biosensor owned an ultrasensitive response (221.0 μA·mM−1·cm−2) in glucose detection under −0.4 V. Such a low operation potential also provided an excellent anti-interference ability to the existence of ascorbic acid and uric acid. This new biosensor with outstanding sensitivity and selectivity can be further developed in trace analysis of more complex detection systems.